Pengaruh Partisipasi Manajer, Pengalaman Kerja Dan Kompleksitas Tugas Terhadap Efektivitas Pengguna Sistem Informasi Akuntansi Pada Perusahaan Daerah Air Minum (PDAM) Kabupaten Tabanan - Komang Arya Suputra; A.A.A Erna Trisna Dewi; Luh Putu Lusi Satyandarini Surya (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2021)
The effectiveness of users of accounting information systems is a measure that provides an overview of the extent to which targets can be achieved from a collection of resources that are arranged to collect, process, and store electronic data, then turn it into useful information and provide the required formal reports with good quality nor time. This study aims to test empirically the effect of manager participation, work experience and task complexity on the effectiveness of users of the accounting information system at the local water company (PDAM) in Tabanan Regency. The theory is the theory of reasoned action (TRA). In this study, it has a population of 314 people with purposive sampling method of determining the sample, so that the sample data amounted to 63 samples. Types and sources of data in this study are quantitative data and qualitative data. The data collection method used in this study was a questionnaire technique. The data analysis technique in this study is multiple linear regression analysis. The results of this study indicate that both simultaneously and partially the variables of managerial participation, work experience and task complexity have a positive effect on the effectiveness of users of the accounting information system at the regional drinking water company (PDAM) of Tabanan Regency.